ENHANCING BASIC ENGLISH SKILLS THROUGH CONTEXTUAL AND PARTICIPATORY LEARNING FOR FEMALE ORPHANS AT TUNAS HARAPAN ORPHANAGE, SITUBONDO - Kamalia, Zakiyah Putri; Hadi, Arini Hubbadiva (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
This community service project aimed to improve the basic English skills of female students at Tunas Harapan PI Orphanage in Situbondo, Indonesia. The program responded to limited access to English education due to insufficient learning support and resources. A contextual and participatory approach was implemented over four weeks, involving 20 participants across various education levels. The methods included language games, songs, role-playing, visual aids, and interactive dialogue. Materials focused on basic vocabulary, pronunciation, and simple sentence construction. A needs assessment informed the lesson design, while formative evaluation tracked learner progress. The results showed increased confidence, vocabulary acquisition, and speaking fluency. A final product, the English Wall Magazine, was created collaboratively to support ongoing learning. This initiative supports previous research on the value of interactive, learner-centered methods in non-formal settings. It also demonstrates that impactful language learning can occur even with limited infrastructure when tailored to the learners’ context and needs.